Human Discrimination of Depth of Field in Stereoscopic and Nonstereoscopic Photographs. (May 2014) - Zhang, Tingting; Nefs, Harold T; Heynderickx, Ingrid
Depth of field (DOF) is defined as the distance range within which objects are perceived as sharp. Previous research has focused on blur discrimination in artificial stimuli and natural photographs. The discrimination of DOF, however, has received less attention. Since DOF introduces blur which is related to distance in depth, many levels of blur are simultaneously present. As a consequence, it is unclear whether discrimination thresholds for blur are appropriate for predicting discrimination thresholds for DOF. We therefore measured discrimination thresholds for DOF using a two-alternative forced-choice task. Ten participants were asked to observe two images and to select the one with the larger DOF. We manipulated the scale of the scene—that is, the actual depth in the scene. We conducted the experiment under stereoscopic and nonstereoscopic viewing conditions. We found that the threshold for a large DOF (39.1 mm) was higher than for a small DOF (10.1 mm), and the thresholds decreased when scale of scene increased. We also found that there was no significant difference between stereoscopic and nonstereoscopic conditions. We compared our results with thresholds predicted from the literature. We concluded that using blur discrimination thresholds to discriminate DOF may lead to erroneous conclusions because the depth in the scene significantly affects people's DOF discrimination ability.